Origin of glacial-fluvial landforms in the Azas Plateau volcanic field, the Tuva Republic, Russia: Role of ice-magma interaction - KOMATSU, Goro; ARZHANNIKOV S. G; ARZHANNIKOVA A. V; ORI, Gian Gabriele (Elsevier BV:PO Box 211, 1000 AE Amsterdam Netherlands:011 31 20 4853757, 011 31 20 4853642, 011 31 20 4853641, EMAIL: nlinfo-f@elsevier.nl, INTERNET: http://www.elsevier.nl, Fax: 011 31 20 4853598, 2007)
The basaltic Azas Plateau volcanic field is located in the Tuva Republic of the Russian Federation. The area was glaciated multiple times, and the field is characterized by the formation of subglacial volcanoes called tuyas, but subaerial volcanoes and lava fields also exist. A combined study of remote sensing and field observations in the vicinity of the tuyas in the southeastern Azas Plateau volcanic field identified landforms that are best explained by the jökulhlaup hypothesis. The landforms include elongated hills, paleochannels, and butte and basin topography. These landforms are hypothesized to have formed by both erosion and deposition caused by high-energy water streams. The triggering for the hypothesized jökulhlaups was either melting of ice by subglacial volcanism and/or destabilization of ice-dammed/subglacial reservoirs. The age estimation of the flood events is difficult, but they probably occurred during the ice ages of the Quaternary, as late as in the Middle-Late Pleistocene.